2019
DOI: 10.1002/ange.201904848
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐Micromolar Pulse Dipolar EPR Spectroscopy Reveals Increasing CuII‐labelling of Double‐Histidine Motifs with Lower Temperature

Abstract: Electron paramagnetic resonance (EPR) distance measurements are making increasingly important contributions to the studies of biomolecules by providing highly accurate geometric constraints.C ombining double-histidine motifs with Cu II spin labels can further increase the precision of distance measurements.Itisalso useful for proteins containing essential cysteines that can interfere with thiol-specific labelling.However,the non-covalent Cu II coordination approachis vulnerable to lowb inding-affinity.H erein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 56 publications
(38 reference statements)
1
38
0
Order By: Relevance
“…As the applications of pulsed dipolar spectroscopy (PDS) broaden, the repertory of spin labels now comprises not only the routinely used nitroxides 7 but also other paramagnetic species. [8][9][10][11] To accommodate the spectral and relaxational differences between these labels, other techniques than the established double electronelectron resonance (DEER) experiment, 12 such as relaxationinduced dipolar modulation enhancement (RIDME) 13,14 and double-quantum coherence (DQC), 15 are stepping into the spotlight. Several examples have also illustrated the advantages of combining spectroscopically orthogonal spin labels, e.g., Cu(II) and nitroxides.…”
mentioning
confidence: 99%
“…As the applications of pulsed dipolar spectroscopy (PDS) broaden, the repertory of spin labels now comprises not only the routinely used nitroxides 7 but also other paramagnetic species. [8][9][10][11] To accommodate the spectral and relaxational differences between these labels, other techniques than the established double electronelectron resonance (DEER) experiment, 12 such as relaxationinduced dipolar modulation enhancement (RIDME) 13,14 and double-quantum coherence (DQC), 15 are stepping into the spotlight. Several examples have also illustrated the advantages of combining spectroscopically orthogonal spin labels, e.g., Cu(II) and nitroxides.…”
mentioning
confidence: 99%
“…Moreover, the disulfide bond generated by the protein‐MTSL conjugates is also unstable in reducing environments. Over the last decade, to overcome the instability of nitroxide radicals, researchers have begun to explore the use of alternative spin labels, based on paramagnetic metal ions, including Cu(II), Mn(II) and Gd(III) . For Mn(II) and Gd(III) spin labels, high‐field (>30 GHz) EPR experiments are preferable, owing to the presence of zero‐field splitting at low fields.…”
Section: Discussionmentioning
confidence: 99%
“…In our own experiments, we have observed that for MTSL spin labels, it is possible to use labeled‐protein concentrations that are as low as 5–10 μM, whereas for Cu(II) spin labels it is necessary to use about 50 μM labeled protein. Nonetheless, recently it was reported of using sub‐micromolar concentrations with Cu(II)‐NTA spin labels . For low protein concentrations, the time‐domain DEER trace is relatively short and is up to 2 μs for nitroxide spin‐labels; therefore distances up to 5.0 nm can be evaluated.…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…[24][25][26][27] Significant progress in performing and analysing Cu(II)-based PDS experiments has been achieved over the past few years. [28][29][30][31][32][33] Exchange interactions are often observed for Cu(II) ions that are bound to conjugated p-systems, [34][35][36][37][38][39] or in strongly coupled systems, such as molecular magnets. 7,40,41 The exchange coupling may give additional information on the system of interest, yet, the dipolar and exchange couplings can become difficult to disentangle.…”
Section: Introductionmentioning
confidence: 99%